The making of a European President - Peñalver García, Nereo, 1983- (Palgrave Macmillan, 2015)
This book tells the inside story of how a "putsch" was organised in a Europe in crisis, how a small group of European politicians from different parties brought about the biggest change in twenty years in the way the EU decides its leadership. The authors describe first-hand Europe's first presidential campaign, the personalities, how the candidates were chosen, the controversies and incidents on the campaign trail, the policy differences, the rallies in the battleground states, the use of social media, and the TV debates. It gives a blow-by-blow account of how Europe's most powerful leading governments were forced to make a humiliating climb-down and accept the election of a leader they did not support, chosen by a process they opposed. But the book also analyses critically this new way of electing the President, what needs to change for 2019, and sets what happened in a broader historical context. A unique trip to the "kitchen" of EU politics